A comparative study of syllables and morphemes as literacy processing units in word recognition: IsiXhosa and SeTswana - Probert, Tracy Nicole (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2016)
Word recognition is a core foundation of reading (Invenizzi and Hayes 2010) and involves interactions of language skills, metalinguistic skills and orthography. The extent of the interaction with one another in reading has yet to be fully explored, especially in the Southern-Bantu languages. This comparative study of isiXhosa and Setswana explores this three-way interaction between language skills (effect of Language of Learning and Teaching (LoLT)), metalinguistic skills (Phonological and Morphological Awareness) and orthography (conjunctivism vs. disjunctivism). This thesis is novel in three respects, (a) a set of linguistic-informed reading measures were developed in isiXhosa and Setswana for the first-time, (b) to my knowledge, the comparisons made and study of Morphological Awareness in the Southern-Bantu languages have never been done, and (c) the use of d-prime as a way of testing for grain size in reading is an innovative approach. Grade 3 and Grade 4 learners were tested on four independent linguistic tasks: an open-ended decomposition task, a Phonological Awareness task, a Morphological Awareness task and an independent reading measure. These tasks were administered to determine the grain size unit (Ziegler and Goswami 2005, Ziegler et al. 2001) which learners use in word recognition, with the grain sizes of syllables and morphemes being studied. Results showed that syllables were the dominant grain size in both isiXhosa and Setswana, with morphemes as secondary grains in isiXhosa. Grain size differed slightly between the two orthographies. These results are reflected in the scores on the metalinguistic tasks. LoLT was not shown to have a significant impact on word recognition in first-language reading. The Psycholinguistic Grain Size Theory (PGST) was found to be the most applicable model of word recognition to the Southern- Bantu languages, as opposed to the Dual-Route Cascade Model and Orthographic Depth Hypothesis. This thesis concludes with suggested adaptations to this theory in order to allow for morpheme grain size to be included. This study has implications for teaching practice and curriculum design, and contributes to a broader understanding of literacy in the foundation phase in the Southern-Bantu languages.
Keywords: Uncatalogued